Threatened by many complex food security problems - agriculture, academic, and government professionals seek new one health research partnerships - Gregory C. Gray; Thang Nguyen-Tien (One Health)
With modern international trade and the rapid movement of people, animals, and food products, today's risks to food security are increasing worldwide. It is clear that human health, animal health, environmental health, and agriculture are inextricable linked. Food security problems in one sector often adversely impact multiple other sectors. Food security threats are often complex with many factors influencing the emergence of new threats. As multiple US governmental agencies share responsibilities for food security threat mitigation, we need to find new ways for the numerous food security scientific disciplines and agencies to forge new effective research collaborations in meeting these threats. This special issue of the journal One Health seeks to give examples of such research. It represents a collection of scientific reports from oral and poster presentations delivered at the April 21–23, 2024, “International Symposium on One Health Research: Improving Food Security and Resilience” in Galveston, Texas.